Identificação e caracterização de elementos retrotransponíveis da família Rex do genoma de espécies do genêro Leporinus SPIX, 1829 (Teleostei: Anostomidae) - Borba, Rafael Splendore de [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
The Anostomidae family is an interesting model for repetitive elements studies, mainly due the presence of high number of heterochromatic segments related to a peculiar system of female heterogamety, which is restricted to a few species belonging to the Leporinus genus. In this way we performed a cytogenetic mapping of retrotransposable elements Rex1, Rex3 and Rex6 in chromosomes of Leporinus: L. elongatus, L. macrocephalus and L. obtusidens, which have sex chromosomes system, and L. friderici, L. lacustris and L. striatus, in order to increase the knowledge of the genomic organization of the genus, observe if these elements are related to heterochromatic regions and whether its distribution is compatible with the hypothesis of a stable macrostructure kept in the karyotype of the genus. Amplification and sequencing of the elements Rex1 and Rex3 showed different compositions regarding the number of base pairs of these elements for these species, but the Rex6 element has not been identified in genome of the species studied. The FISH technique using Rex1 element as probe resulted different distribution pattern: Leporinus elongatus, L. macrocephalus and L. obtusidens presented clusters isolated in the terminal region and the others species present signals disperse in all chromosomes and some signals on terminal position. The Rex3 signals are accumulated mainly in terminal position in all chromosomes for all species. The W chromosome of L. elongatus, L. macrocephalus and L. obtusidens, presents Rex3 signal on interstitial position. Some variations were observed regarding the hybridization signals among species. These results suggest the occurrence of different levels of activity of these elements during the evolutive process of the species analyzed. Despite the quite conserved karyotypic macrostructure of Leporinus species, through our results was possible to observe some variation on hybridization signals pattern, specially among the group...

A família Anostomidae é um interessante modelo para estudos de elementos repetitivos, principalmente devido à presença de elevado número de segmentos heterocromáticos relacionados a um sistema peculiar de heterogametia feminina, que é restrita a algumas espécies pertencentes ao gênero Leporinus. Nesse sentido, este trabalho teve como objetivo realizar um mapeamento cromossômico dos elementos retrotransponíveis Rex1, Rex3 e Rex6 nos cromossomos de seis espécies do gênero Leporinus: L. elongatus, L. macrocephalus e L. obtusidens, as quais possuem sistema de cromossomos sexuais, e L. friderici, L. lacustris e L. striatus, a fim de aumentar o conhecimento a respeito da organização do genoma do gênero, observar a relação desses elementos com regiões heterocromáticas importantes e se a distribuição é compatível com a hipótese de uma macroestrutura cariotípica estável para o gênero. A amplificação e o sequenciamento dos elementos Rex1 e Rex3, mostraram diferentes composições referentes ao número de pares de bases destes elementos para as diferentes espécies analisadas, já o elemento Rex6 não foi identificado no genoma das espécies estudadas. A técnica de FISH utilizando o elemento Rex1 como sonda resultou em diferentes padrões de distribuição: Leporinus elongatus, L. macrocephalus e L. obtusidens apresentaram clusters isolados na região terminal e as outras espécies apresentaram sinais dispersos em todos os cromossomos e pequenos sinais na posição terminal de alguns cromossomos. O elemento Rex3 se apresentou acumulado principalmente na posição terminal, em todos os cromossomos de todas as espécies. O cromossomo W de L. elongatus, L. macrocephalus e L. obtusidens, apresenta um sinal positivo de Rex1 e Rex3 na posição intersticial do braço longo. Algumas variações de sinais de hibridação foram observadas entre as diferentes espécies. Estes resultados sugerem a ocorrência de diferentes graus de...
Keywords: Fishes; Peixe; Mapeamento cromossômico; Citogenética animal; DNA; Cromossomos sexuais; Piava (Peixe)